Literature Review: Pengaruh Kebiasaan Jajan dan Higienitas Jajanan terhadap Kejadian Diare pada Anak SD - Rina Priastini Susilowati; Budiman Hartono; Bryan Reyes Stephen (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Consuming street food is a habit common among elementary school students. Snacking habits can be influenced by parents and friends, and various other factors. The hygiene of the snacks in school environment is also a consideration. This study aims to determine the effect of snacking habits and snacks hygiene on incidence of diarrhea among elementary school students. The study was conducted by comparing available data from six journals. The results showed conflicting data on the effect of snacking habits on incidence of diarrhea with two sources showing significant (p < 0.05) and insignificant (p > 0.05) impact. Hand washing habits (p < 0.05), carrying meals (p < 0.05), and knowledge (p < 0.05) had a significant influence on snacking habits and incidence of diarrhea. For snack hygiene, food quality (p < 0.05); storage (p < 0.05); and processing (p < 0.05); sanitation facilities (p < 0.05); and food handlers’ hygiene (p < 0.05) had a significant effect on E.coli contamination. Apart from hygiene, some snacks were found to contain harmful food additives. In conclusion, it is necessary to conduct an educational program for healthy snacks as well as monitor and maintain canteen hygiene on a regular basis.